Hiding Making - Showing Creation The Studio from Turner to Tacita Dean - Esner, Rachel; Lehmann, Ann-Sophie; Kisters, Sandra (Amsterdam University Press, 2013)
The aim of Hiding Making - Showing Creation is twofold. In the first instance, we seek to trace the Nachleben of these studio topoi from the nineteenth century to today, in particular focusing on how artists have employed them as strategies for showing certain aspects of their practice (above all those which perpetuate the notions of artistic genius and autonomy), while carefully hiding others from view (routine, failure, craft). Secondly, in order to achieve these goals, we have adopted a method that we feel not only does justice to the richness and diversity of the topic but which, we believe, will add a new dimension to the already abundant and ever growing literature on the artist's studio.